Storage study of flat piaya packed in oriented polypropelene bag, metallized bag and vaccum bag - Navarro, Jhoanna Dumdumaya (2010.)
Storage study of flat piaya packed in oriented polypropylene bag (OB), metallized bag (MB), and vacuum bag (VB) was evaluated by monitoring physico-chemical properties, microbiological properties (yeast and molds count) and sensory qualities during storage at room temperature (28 - 32 degree celcius).
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Piaya